A guide to the valid names of Lumbricidae (Oligochaeta) - Easton, E. G. ([Book chapter], 1983)
Provisional list of Lumbricidae valid names up to December, 1981
Table 41.3 "Changes in taxonomy and nomenclature" follows the references